(untitled) (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of MBCT (Mindfulness Based Cognitive Therapy) intervention on stress and coping with premenstrual syndrome. The research method is a quasi-experiment within two groups with a pretest-posttest control group design. The results showed that the Mindfulness-Based Cognitive Therapy (MBCT) Intervention affected stress (p 0.000 <0.015) and had an effect on coping with premenstrual syndrome (P 0.049 <0.05) compared to the control group. The conclusion is that the Mindfulness-Based Cognitive Therapy (MBCT) Intervention has an effect on stress and coping with premenstrual syndrome for four weeks consisting of 4 meeting sessions with a duration of 60 minutes per meeting so that it can be applied as an alternative holistic therapy for sufferers of premenstrual syndrome. Keywords: Coping with Premenstrual Syndrome, MBCT, Premenstrual Syndrome, Stress